Menjamin Kehalalan Produk Unggas: Analisis Sertifikasi Halal pada RPU King Broiler Mojokerto - Muhammad Ghufron; Aslikha Aslikha; Sukamto Sukamto (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Halal certification in poultry slaughterhouses has become an important instrument in ensuring product quality, consumer protection, and compliance with halal regulations in Indonesia. The implementation of halal certification at King Broiler Poultry Slaughterhouse (RPU) Mojokerto reflects not only administrative compliance but also the integration of halal principles into operational management. Using a qualitative case study approach, data were collected through semi-structured interviews, direct observation, and documentation involving managers, halal slaughterers, and production workers. The analysis employed the Halal Product Assurance System (SJPH) framework, covering commitment and responsibility, materials, halal production process, products, and monitoring and evaluation. The findings indicate that the slaughtering process constitutes the most critical point in maintaining halal integrity, particularly regarding the condition of live chickens, slaughtering procedures, tool hygiene, and post-slaughter handling. Challenges remain in documentation management, workers’ understanding of halal standards, and the consistency of internal supervision. Strengthening efforts have been carried out through employee training, improved documentation systems, facility hygiene maintenance, and periodic evaluation. Consistent implementation of SJPH contributes to enhancing halal compliance, product quality, operational management, and consumer trust in poultry products.